Instabilities in binary compounds under irradiation - Mykhaylovskyy, V.V.; Sugakov, V.I. (Вопросы атомной науки и техники, 2000)
A simulation of radiation-induced instability in binary semiconductor, such as GaAs, was fulfilled. The instability is connected with antisite defects accumulated. It was shown that the number of antisite defects in crystal under irradiation can significantly exceed their equilibrium concentration. We have found that the instability with respect to periodical defect distribution appear at some conditions of irradiation. The wavelenght of the periodical distribution was estimated as 100 nm - 10 nm depending on crystal parameters . Моделирование радиационно-индуцированной нестабильности в двоичной полупроводника, например, GaAs, было выполнено.Нестабильность связана с антиструктурных дефектов накапливается. Было показано, что число антиструктурных дефектов в кристалле при облучении может значительно превышать их равновесная концентрация. Мы обнаружили, что неустойчивость по отношению к периодического распространения дефектов появляются в некоторых условиях облучения.Длина волны периодического распределения была оценена как 100 нм - 10 нм в зависимости от параметров кристаллической. Моделювання радіаційно-індукованої нестабільності в двійковій напівпровідника, наприклад, GaAs, було виконано. Нестабільність пов'язана з антиструктурних дефектів накопичується. Було показано, що число антиструктурних дефектів в кристалі при опроміненні може значно перевищувати їх рівноважна концентрація. Ми виявили, що нестійкість по відношенню до періодичного поширення дефектів з'являються в деяких умовах опромінення. Довжина хвилі періодичного розподілу була оцінена як 100 нм - 10 нм залежно від параметрів кристалічної.